Factors predictive of leg‐ulcer healing in sickle cell disease: a multicentre, prospective cohort study. (26th April 2017) - Senet, P.; Blas‐Chatelain, C.; Levy, P.; Manea, E.M.; Peschanski, M.; Mirault, T.; Stankovic‐Stojanovic, K.; Debure, C.; Debbache, K.; Girot, R.; Bureau, J.‐M.; Bachmeyer, C.; et al.
Summary: Background: Leg ulcers (LUs) are a chronic and severe complication of sickle cell disease (SCD). A prospective study in patients with SCD to identify factors associated with complete healing and recurrence of LUs is lacking. Objectives: To determine clinical and biological factors associated with SCD‐LU complete healing and recurrence. Methods: This prospective, observational cohort study was conducted at two adult SCD referral‐centre sites (2009–2015) and included 98 consecutive patients with at least one LU lasting ≥ 2 weeks. The primary end points compared patients with healed vs. nonhealed LUs at week 24, and patients with vs. without recurrence during follow‐up. Results: The median (interquartile range) LU area, duration and follow‐up were, respectively, 6·2 cm 2 (3–12·8), 9 weeks (4–26) and 65·8 weeks (23·8–122·1). At week 24, LUs were healed in 47% of patients, while 49% of LUs recurred. Univariate analyses identified inclusion LU area < 8 cm 2 (82% vs. 35%; P < 0·001), inclusion LU duration < 9 weeks (65% vs. 35%; P = 0·0013) and high median fetal haemoglobin level ( P = 0·008) as being significantly associated with complete healing at week 24, and low lactate dehydrogenase level ( P = 0·038) as being associated with recurrence. Multivariate analyses retained LU area < 8 cm 2 (odds ratio 6·73, 95% confidence interval 2·35–19. 31; P < 0·001) and < 9 weeks' duration (OR 3·19, 95% confidence interval 1·16–8·76; P = 0·024) as being independently associated with healing at week 24. Factors independently associated with recurrence could not be identified. Conclusions: SCD‐LU complete healing is independently associated with the clinical characteristics of LUs rather than the clinical or biological characteristics of SCD. Abstract : What's already known about this topic? Factors predictive of sickle cell disease (SCD)‐related leg‐ulcer (LU) healing are not known, although their identification would seem to be essential for therapeutic decisions and clinical research. What does this study add? At week 24, LUs were completely healed in 47% of the patients, with 15 weeks being the median time to healing. Healing prognosis was independently linked to LU area < 8 cm 2 and duration < 9 weeks, but not to SCD characteristics. Respond to this article Linked Comment: Aractingi. Br J Dermatol 2017;177 :15–16 Plain language summary available online